Carrier Attitude Adjustment Strategy of a Space Robot for On-Orbit Detection. (5th February 2016) - Wu, Jianwei; Zhang, Yin; Cui, Jiwen; Tan, Jiubin
A strategy for attitude adjustment of a free-floating space robot is proposed to reduce fuel consumption and time required to operate a space manipulator and its carrier before and after the detection of an on-orbit spacecraft. This strategy can be used in such a way that the carrier attitude and space manipulator joint angle reach their expected values at the same time. In order to obtain an advanced effect of carrier attitude adjustment, a novel parameterization method of joint trajectory is proposed, which extends the search scope of the joint trajectory by the fusion of the 4-3-4 and 3-5-3 planning methods. An objective function is defined according to the difference of the expected and initial carrier attitudes. A genetic algorithm is used to search for an optimal solution of the parameters. The effectiveness of the proposed strategy is verified through simulations for a six-degree-of-freedom (6-DOF) space robot system.